Analisis Penggunaan Think Pair Share dan Berpikir Kreatif dalam Pengembangan Kompetensi Profesional Guru Pendidikan Agama Islam di Kecamatan Leuwiliang - Thoni Anthoni Mukti Prasetyo; Ami Primarni; Riyanto (Jurnal Dirosah Islamiyah, 2024)
This study aims to analyze the implementation of the Think Pair Share (TPS) strategy and creative thinking skills in the development of professional competence of Islamic Religious Education (PAI) teachers in Leuwiliang District. The research approach used is descriptive qualitative, with data collected through observation, in-depth interviews, and document analysis in nine elementary schools in the region. The results of the study show that the implementation of TPS effectively increases student engagement during the learning process, supports the enhancement of teachers' professional competence, particularly in classroom management, and deepens understanding and mastery of teaching materials.In the context of education, Islam emphasizes the importance of knowledge, as mentioned in QS. Al-Mujadilah: 11: يَرْفَعِ اللَّهُ الَّذِينَ آمَنُوا مِنكُمْ وَالَّذِينَ أُوتُوا الْعِلْمَ دَرَجَاتٍ"Allah will raise those who believe among you and those who have been given knowledge by degrees." However, the study also found several challenges in the implementation of this strategy, including limited school facilities and the lack of formal training received by teachers related to the application of TPS. This study provides recommendations for improving the quality of education in Leuwiliang District, emphasizing the importance of continuous training for teachers and improving educational facilities to ensure that innovative learning methods such as TPS can be applied more effectively.